2019
DOI: 10.1017/s1368980019001861
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and overweight risk among Malaysian adults: evidence from nationally representative surveys

Abstract: Objective:To investigate the association between dietary patterns (DP) and overweight risk in the Malaysian Adult Nutrition Surveys (MANS) of 2003 and 2014.Design:DP were derived from the MANS FFQ using principal component analysis. The cross-sectional association of the derived DP with prevalence of overweight was analysed.Setting:Malaysia.Participants:Nationally representative sample of Malaysian adults from MANS (2003, n 6928; 2014, n 3000).Results:Three major DP were identified for both years. These were ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…This finding also justifies the permanence of the association of dietary patterns with obesity in women, but not in men from the Brazilian region evaluated in this study. Finally, also in agreement with our findings, unhealthy dietary patterns had no significant association with abdominal obesity [ 88 , 89 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding also justifies the permanence of the association of dietary patterns with obesity in women, but not in men from the Brazilian region evaluated in this study. Finally, also in agreement with our findings, unhealthy dietary patterns had no significant association with abdominal obesity [ 88 , 89 ].…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, this is the first population-based study that assessed adherence to dietary patterns determined a posteriori and its association with obesity and abdominal obesity in a rural area, taking into account the labor aspects of farmers. However, in the general population, some studies that evaluated dietary patterns using this method [ 87 , 88 ], including meta-analyses [ 69 , 70 ], also identified that greater adherence to healthier dietary patterns (often represented by traditional dietary patterns) was associated with a lower risk of obesity. Individuals in the highest categories of adherence to these healthy dietary patterns were 36% less likely to have general obesity (OR = 0.64; 95% CI = 0.52–0.78; P < 0.001) [ 90 ] and 19% less likely to have central obesity (OR = 0.81; 95% CI = 0.66–0.96; P < 0.001) [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eating foods high in saturated fat, trans fat, salt, and sugar is also associated with a high risk of CVD. Previous studies conducted among Malaysians showed that Malays had poor eating habits associated with the risk of developing CVD [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eating foods high in saturated fat, trans fat, salt, and sugar are also associated with a high risk of CVD. Previous studies conducted among Malaysians showed that Malays had poor eating habits associated with the risk of developing CVD 33,34 .…”
Section: Discussionmentioning
confidence: 99%